Post-Treatment of Micro-Needling with a Dexpanthenol-Containing Ointment Accelerates Epidermal Wound Healing in Human 3D Skin Models - Weßollek K; Marquardt Y; Wagner-Schiffler S; Baron JM; Huth S (Dove Medical Press, 2023)
Katharina Weßollek,1 Yvonne Marquardt,1 Sylvia Wagner-Schiffler,2 Jens Malte Baron,1,* Sebastian Huth1,* 1Department of Dermatology and Allergology, University Hospital RWTH Aachen, Aachen, Germany; 2Praxis für Dermatologie, Aachen, Germany*These authors contributed equally to this workCorrespondence: Katharina Weßollek, Department of Dermatology and Allergology, University Hospital RWTH Aachen, Aachen, Germany, Tel +49 241 7501 8240, Fax +49 241 7501 8290, Email kwessollek@ukaachen.dePurpose: In vitro study on the molecular effects of post-treatment after micro-needling applications with a dexpanthenol-containing ointment (DCO) using 3D skin models.Patients and Methods: In this in vitro study, full-thickness human 3D skin models were treated with a micro-needling device according to its clinical application. For post-treatment, some of the models were additionally treated with a dexpanthenol-containing ointment (DCO). Histological samples were taken at 0, 24 and 48 hours. Gene expression analysis was performed after 24 hours.Results: Histological examination showed that DCO post-treated 3D skin models revealed a completed wound closure 24 hours after the micro-needling procedure. In contrast, DCO-untreated models still clearly exhibited the micro-needling lesions after the same period of time. After 48 hours, all models revealed a completed wound healing. In skin models that received micro-needling but no post-treatment with DCO, microarray analysis identified an upregulation of proinflammatory cytokines and chemokines and a downregulation of skin barrier and differentiation markers. In contrast, post-treatment with DCO leads to accelerated wound healing without affecting the initial inflammatory response caused by micro-needling, which leads to the subsequent collagen expression. This data was supported by qRT-PCR analyses.Conclusion: Post-treatment with DCO accelerates epidermal wound healing after micro-needling of 3D skin models without impairing the immunostimulatory properties of micro-needling. These findings can help to optimise the aftercare routine after micro-needling procedures and to shorten the downtime for the patient after treatment.Keywords: in vitro models, cosmetic procedures, aftercare, skin needling, molecular effects, human organotypic skin equivalents